2014
DOI: 10.1080/15226514.2013.828014
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Landfill Leachate withColocasia esculenta, Gynerum sagittatumandHeliconia psittacorumin Constructed Wetlands

Abstract: This study assessed the accumulation of Cd (II), Hg (II), Cr (VI) and Pb (II) in Gynerium sagittatum (Gs), Colocasia esculenta (Ce) and Heliconia psittacorum (He) planted in constructed wetlands treating synthetic landfill leachate. Sixteen bioreactors were operated in two experimental blocks. Metal concentrations in the influent and effluent; root, stem, branch and leaves of plants were analysed, as well as COD, N-NH4+, TKN, T, pH, ORP, DO, and EC. Average removal efficiencies of COD, TKN and NH4+-N were 66, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(43 citation statements)
references
References 21 publications
1
32
0
7
Order By: Relevance
“…These proteins favor the transport of metals from roots to shoots (Iqbal et al, 2015). Several studies demonstrated the metal tolerance and phytoextraction efficiency of arum plant to various heavy metals such as Cd, Pb and Zn (Kashem et al, 2008;Kim et al, 2011;Kashem et al, 2013;Chayapan et al, 2015a;2015b;Madera-Parra et al, 2015;Islam et al, 2016a;2016b). Chayapan et al (2015b) metals like Cd (II), Hg (II), Cr (VI), and Pb (II), and still showed healthy growth in constructed wetlands treating synthetic landfill leachate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These proteins favor the transport of metals from roots to shoots (Iqbal et al, 2015). Several studies demonstrated the metal tolerance and phytoextraction efficiency of arum plant to various heavy metals such as Cd, Pb and Zn (Kashem et al, 2008;Kim et al, 2011;Kashem et al, 2013;Chayapan et al, 2015a;2015b;Madera-Parra et al, 2015;Islam et al, 2016a;2016b). Chayapan et al (2015b) metals like Cd (II), Hg (II), Cr (VI), and Pb (II), and still showed healthy growth in constructed wetlands treating synthetic landfill leachate.…”
Section: Discussionmentioning
confidence: 99%
“…There are several studies that have demonstrated the metal tolerance and phytoextraction efficiency of arum (C. esculenta L., C. antiqourum L.) and other plant species to various heavy metals such as Cd, Zn, Pb etc. (Yanqun et al, 2005;Kashem et al, 2008;Castiglione et al, 2009;Wang et al, 2009;Kashem et al, 2010;Kim et al, 2011;Kashem et al, 2013;Chayapan et al, 2015a;2015b;Madera-Parra et al, 2015;Nahar and Alam, 2015;Islam et al, 2016a;2016b). Chayapan et al (2015b) investigated phytoremediation potential of Cd and Zn by wetland plants, C. esculenta L., Schott., Cyperus malaccensis Lam.…”
Section: Introductionmentioning
confidence: 99%
“…Translocation factors (TFs) were lower; He was the plant exhibiting TFs >1 for Pb(II), Cr(T), and Hg(II) and 0.4-0.9 for Cd(II) and Cr(VI). The evaluated plants demonstrate their suitability for phytoremediation of landfi ll leachate, and all of them can be categorized as metal accumulators (Madera et al 2015). Ascúntar et al ( 2009 ) assessed a pilot-scale HSSF CW planted with Phragmites australis and Heliconia psittacorum (Fig.…”
Section: Experiences Of Phytoremediation In Colombiamentioning
confidence: 99%
“…Gutiérrez (2009a) registró un mejor desempeño de estas plantas en la eliminación de DOQ y DBO 5 para la condición de más alta carga contaminante aplicada al reactor sembrado con la especie Heliconia sp, situación igualmente reportada por Madera et al, (2013). Montoya et al, (2010), encontraron que en la eliminación de DQO, COD y DBO 5 , no habían diferencias entre las especies Heliconia sp y Phragmities au, indicando que el uso de la especie nativa además de mantener las mismas condiciones operacionales de la tecnología, permite crear ambientes agradables como ornamentación por las floración que dicha especie produce.…”
Section: +unclassified
“…Recientemente, estudios han evaluado el papel de esta especie en la remediación de aguas residuales encontrando efectos positivos en la bioremediación (Ascuntar & Toro 2007, Gomez & Segura 2008, Gutiérrez 2009a2009b, Sandoval 2009, Peña et al, 2011. Estas evidencias muestran una cierta tolerancia de H. psittacorum a un amplio espectro de condiciones ambientales, por lo que la hace una especie atractiva para su uso en sistemas naturales como los humedales construidos subsuperficiales (HC) para el tratamiento de aguas residuales (Brisson y Chazarenc, 2009, Maza, 2006, Madera et al, 2013.…”
Section: Introductionunclassified